What is an ABI?. (2nd December 2022) - Morley, Emily; Bennett, Emily; Costello, Gemma
Abstract : The authors of this article, psychologists and representatives of N-ABLES, introduce ABI and the symptoms, with examples of what this may look like in children, and they discuss the need for change around the lack of awareness of this injury.